Reinventing Budgeting: The Impact of Third Way Modernisation on Local Government Budgeting - W. B. Seal, Amanda Ball* (Elsevier, 2008)
The focus of this project was on New Labour 1997–2003 policy innovations for the sector and their impact on traditional, incrementalist budgeting practices. The most recent initiative is the ‘Comprehensive Performance Assessment ’ (CPA) whereby the Audit Commission ranks the corporate performance of authorities rather than just evaluating individual service areas as under the ‘Best Value ’ regime. The central question motivating the report was: What is the extent to which it is possible or useful to reform traditional, incrementalist budgeting practices? The project was based on a longitudinal field study of budgetary practice in two large but very contrasting English local authorities. Officials in the Office of the Deputy Prime Minister and at the Audit Commission were also interviewed.